The Right to Death. Fiction or Reality? - LUCAN, Maria Casandra (Journal of Legal Studies, 2016)
The present article is part of a dense literature – result of a perennial debate – that has polarized societies for a long time and has evident reverberations in the present. It deals with "the right to death", trying to offer some answers referring to its existence in fact and the way in which it is perceived by different states and diverse entities with juridical nature. In the first part of the paper, it is insisted upon the right to life, so that subsequently, to speak in detail about a "right to death" and the moral and juridical implications of using such phrases. There are analyzed different states of the world found on one part or the other of the barricade in what concerns the legality of euthanasia and assisted suicide – considered the two hypostasis of the right in question. It is offered, as well, an analysis of the Convention for the Protection of Human Rights and Fundamental Freedoms, mentioning that, paradoxically, while it cannot be modified so that it allows the appearance of some new rights, it can tacitly accept the creation by some states that have adhered to it of some rights antagonistic with those presented in its text. The conclusion, is that not any liberalization movement of a social action – quantified through the request of a right – has as a direct result a progress of the respective society, especially when the action creates something diametrically opposed to some fundamental functioning norms, such as, by excellence, the granting of the protection of life of all individuals.